Synthesis, in silico and antimicrobial activity study of substituted aromatic imines and their corresponding amines - Hanna Abbo; Darin Edward Holman; Mohamed-Deen Hendricks; Christiana Abimbola Salubi; Marshall Keyster; Salam Titinchi (Results in Chemistry)
The antimicrobial properties of Schiff bases and their corresponding amines were assessed by exploring the impact of substituent variations on these activities. The present study involved the synthesis of Schiff base compounds and their corresponding sec-amines, characterization, antibacterial testing, and molecular docking studies. These compounds featured diverse structural components, including alkyl chains, phenyl and methoxy groups. Three of the synthesized compounds are new, viz. N-[(2,3-dimethoxyphenyl) methylene]-1-propanamine (1), N-[(2,3-dimethoxyphenyl)methyl]-1-propanamine (2) and N-[(2,3-dimethoxyphenyl)methylene]-1-butanamine (3). The assessment of antibacterial properties targeted two strains recognized as opportunistic pathogens. Notably, all Schiff base compounds possessing the −C=N moiety exhibited good antibacterial activity against P. aeruginosa and P. agglomerans. Specifically, 1 and 3 demonstrated exceptional effectiveness against the tested bacterial strains, showcasing promising antibacterial capabilities. Furthermore, binding energy calculations revealed that compounds 1 and 3 exhibited binding energies of −3.9, −4.1, and −3.8, −3.9 kcal/mol with respect to P. agglomerans and P. aeruginosa candidate proteins, respectively. This underscores the strong interaction between the synthesized compounds and the bacterial strains, further supporting their potential as potent antimicrobial agents. P. aeruginosa and P. agglomerans were found to be sensitive to both compounds 1 and 3, as well as the standard control ampicillin. The MIC values for P. aeruginosa were 10 mM for 1, and 6 mM for 3. While for P. agglomerans, the MIC values were 6 mM for both 1 and 3.